Identification of the structural genes for glutamate synthase and genetic characterization of this region of the Salmonella typhimurium chromosome. - Fuchs, R L (1982)
Salmonella typhimurium cells require glutamate synthase activity for growth in media containing a growth rate-limiting nitrogen source. Although this enzyme plays a critical role in ammonia assimilation, little is known about the organization and regulation of the structural genes for its two subunits. To identify the location of the structural genes, mutants having heat-labile glutamate synthase activities were isolated and characterized. Mutations that altered glutamate synthase activity were mapped at 69 U on the S. typhimurium chromosome. Four strains with independent Tn10 insertions in this region were constructed and used for mutant selection and for positioning mutations affecting glutamate synthase activity relative to other genetic markers. In contrast to results obtained with Escherichia coli mutants, there was no linkage between mutations affecting glutamate synthase activity and the argG gene. The results of a combination of transduction experiments demonstrated the gene order argG-glnF-gltB-cod-argR-envB-aroE for S-typhimurium.